Genetic diversity, evolution and selection in the major histocompatibility complex DRB and DQB loci in the family Equidae - Klumplerova, Marie; Splichalova, Petra; Oppelt, Jan; Futas, Jan; Kohutova, Aneta; Musilova, Petra; Kubickova, Svatava; Vodicka, Roman; Orlando, Ludovic; Horin, Petr (BMC genomics, 2020)
BACKGROUND: The mammalian Major Histocompatibility Complex (MHC) is a genetic region containing highly polymorphic genes with immunological functions. MHC class I and class II genes encode antigen-presenting molecules expressed on the cell surface. The MHC class II sub-region contains genes expressed in antigen presenting cells. The antigen binding site is encoded by the second exon of genes encoding antigen presenting molecules. The exon 2 sequences of these MHC genes have evolved under the selective pressure of pathogens. Interspecific differences can be observed in the class II sub-region. The family Equidae includes a variety of domesticated, and free-ranging species inhabiting a range of habitats exposed to different pathogens and represents a model for studying this important part of the immunogenome. While equine MHC class II DRA and DQA loci have received attention, the genetic diversity and effects of selection on DRB and DQB loci have been largely overlooked. This study aimed to provide the first in-depth analysis of the MHC class II DRB and DQB loci in the Equidae family. RESULTS: Three DRB and two DQB genes were identified in the genomes of all equids. The genes DRB2, DRB3 and DQB3 showed high sequence conservation, while polymorphisms were more frequent at DRB1 and DQB1 across all species analyzed. DQB2 was not found in the genome of the Asiatic asses Equus hemionus kulan and E. h. onager. The bioinformatic analysis of non-zero-coverage-bases of DRB and DQB genes in 14 equine individual genomes revealed differences among individual genes. Evidence for recombination was found for DRB1, DRB2, DQB1 and DQB2 genes. Trans-species allele sharing was identified in all genes except DRB1. Site-specific selection analysis predicted genes evolving under positive selection both at DRB and DQB loci. No selected amino acid sites were identified in DQB3. CONCLUSIONS: The organization of the MHC class II sub-region of equids is similar across all species of the family. Genomic sequences, along with phylogenetic trees suggesting effects of selection as well as trans-species polymorphism support the contention that pathogen-driven positive selection has shaped the MHC class II DRB/DQB sub-regions in the Equidae.
Keywords: Family Equidae; Trans-species polymorphism; Equidae; Selection, Genetic; Animals; vznik druhů (genetika); MHC class II loci; polymorfismus genetický; Positive selection; selekce (genetika); Evolution, Molecular; Major histocompatibility complex; rekombinace genetická; Genetic Speciation; Polymorphism, Genetic; zvířata; fylogeneze; Recombination, Genetic; Major Histocompatibility Complex; Selected amino acid sites; hlavní histokompatibilní komplex; Phylogeny; MHC exon 2; molekulární evoluce